Evaluating Targeted Therapeutic Response With Predictive Blood-Based Biomarkers in Patients With Chronic Mild Traumatic Brain Injury - Shawn R. Eagle; Ava M. Puccio; Denes V. Agoston; Ryan Soose; Michael Mancinelli; Rachel Nwafo; Peyton McIntyre; Allison Agnone; Savannah Tollefson; Michael Collins; Anthony P. Kontos; Walter Schneider; et al. (Neurotrauma Reports, 2023)
Chronic consequences of mild traumatic brain injury (mTBI) are heterogeneous, but may be treatable with targeted medical and rehabilitation interventions. A biological signature for the likelihood of response to therapy (i.e., ?predictive? biomarkers) would empower personalized medicine post-mTBI. The purpose of this study was to correlate pre-intervention blood biomarker levels and the likelihood of response to targeted interventions for patients with chronic issues attributable to mTBI. Patients with chronic symptoms and/or disorders secondary to mTBI >3 months previous (104 days to 15 years; n?=?74) were enrolled. Participants completed pre-intervention assessments of symptom burden, comprehensive clinical evaluation, and blood-based biomarker measurements. Multi-domain targeted interventions for specific symptoms and impairments across a 6-month treatment period were prescribed. Participants completed a follow-up testing after the treatment period. An all-possible model's backward logistic regression was built to identify predictors of improvement in relation to blood biomarker levels before intervention. The minimum clinically important difference (MCID) of the change score (post-intervention subtracted from pre-intervention) for the Post-Concussion Symptom Scale (PCSS) to identify treatment responders from non-responders was the primary outcome. The MCID for total PCSS score was 10. The model to predict change in PCSS score over the 6-month intervention was significant (R2?=?0.09; p?=?0.01) and identified ubiquitin C-terminal hydrolase L1 (odds ratio [OR]?=?2.53; 95% confidence interval [CI], 1.18?5.46; p?=?0.02) and hyperphosphorylated tau (p-tau; OR?=?0.70; 95% CI, 0.51?0.96; p?=?0.03) as significant predictors of symptom improvement beyond the PCSS MCID. In this cohort of chronic TBI subjects, blood biomarkers before rehabilitation intervention predicted the likelihood of response to targeted therapy for chronic disorders post-TBI.